Labor Law Analysis of the Implementation of Menstrual Leave for Female Workers - Zimah, Amelia Abdullah; Kansil, Christine S T (CV. Rayyan Dwi Bharata, 2024)
Menstruation is a biological function that occurs naturally and is important in contributing to reproduction for all women. Even though it is a reproductive function that is experienced naturally by women, the experience of menstruation can vary, from mild symptoms to severe symptoms. As a result of menstrual symptoms on the first and second day experienced by almost all women, this causes their activities, performance and quality of life to be disrupted. This is a consideration for the Government to implement menstrual leave for companies in Indonesia. Menstrual leave was implemented by the government in labor law No.13 of 2003. The creation of labor law regulations was nothing more than a relief to working conditions for female workers. Although the law recognizes the right to menstrual leave, there are many obstacles to exploiting the right which requires a lot of practical activities and a deep understanding of more real situations or actions.